SR-BI Mediated Transcytosis of HDL in Brain Microvascular Endothelial Cells Is Independent of Caveolin, Clathrin, and PDZK1 - Fung, Karen Y.; Wang, Changsen; Nyegaard, Steffen; Heit, Bryan; Fairn, Gregory D.; Lee, Warren L. (Frontiers in Physiology, 2017)
The vascular endothelium supplying the brain exhibits very low paracellular and transcellular permeability and is a major constituent of the blood-brain barrier. High-density lipoprotein (HDL) crosses the blood-brain barrier by transcytosis, but technical limitations have made it difficult to elucidate its regulation. Using a combination of spinning-disc confocal and total internal reflection fluorescence microscopy, we examined the uptake and transcytosis of HDL by human primary brain microvascular endothelial cell monolayers. Using these approaches, we report that HDL internalization requires dynamin but not clathrin heavy chain and that its internalization and transcytosis are saturable. Internalized HDL partially co-localized with the scavenger receptor BI (SR-BI) and knockdown of SR-BI significantly attenuated HDL internalization. However, we observed that the adaptor protein PDZK1—which is critical to HDL-SR-BI signaling in other tissues—is not required for HDL uptake in these cells. Additionally, while these cells express caveolin, the abundance of caveolae in this tissue is negligible and we find that SR-BI and caveolin do not co-fractionate. Furthermore, direct silencing of caveolin-1 had no impact on the uptake of HDL. Finally, inhibition of endothelial nitric oxide synthase increased HDL internalization while increasing nitric oxide levels had no impact. Together, these data indicate that SR-BI-mediated transcytosis in brain microvascular endothelial cells is distinct from uptake and signaling pathways described for this receptor in other cell types.